Hubungan Kelengkapan Isi Asesmen Awal Pasien dan Tema Komplain Pasien - Mahabara Yang Putra; Luky Dwiantoro; Septo Pawelas Arso (Magister Kesehatan Masyarakat, Fakultas Kesehatan Masyarakat, Universitas Diponegoro, 2022)
ABSTRACTBackground: The hospital is a plenary individual health service with one of the service standards in the form of patient assessment. The incomplete rate of filling out the initial medical assessment of patients in April 2018 at the inpatient polyclinic reached 37.35% from the standard which should have been 0% incomplete in 1x24 hours. The purpose of this study was to analyze the relationship between the level of completeness of the patient's initial assessment with the patient's complaint theme area. Method: This research is an analytical descriptive study used total sampling. Data were collected from December 2020 to February 2021. The research variable used was the level of completeness of the initial patient assessment as an independent variable with the patient's complaint theme field as the dependent variable. Data analysis was performed using a frequency distribution table and relationship analysis using the chi-square test.Results: The most (67.2%) complaints were made by patients or their families with incomplete initial assessments. The highest complaints with incomplete initial assessment were found in the medical field (75.0%). There was no relationship between the level of completeness of the patient's initial assessment and the patient's complaint theme area (p-value = 0.680). Evaluation of the hospital is needed to improve the quality of service. Further research can be conducted to determine the factors causing the high number of complaints in the medical field.Keywords: patient assessment, complaint, hospital